Estimativas dos momentos estatísticos para o problema de flexão estocástica de viga em uma fundação Pasternak - Santos, Marcelo Borges dos (2015)
This work proposes the resolution of stochastic bending problem in a Euler- Bernoulli beam, on a foundation type Pasternak, through a computational method based on Monte Carlo simulation. Uncertainty is present in the elastic coefficients of the beam and foundation. First, it is established the mathematical formulation of the problem which is derived from a physical model displacement of the beam, that takes into account the influence of the foundation on the problem of response. This requires an approach that is made up on the most common models of foundation, which are: the model Winkler type and model of Pasternak.In sequence we study the existence and uniqueness of the variational problem. To obtain the solution of the problem, a mathematical reasoning is carried out, to the following matters: representation of uncertainty, Galerkin method, serial Neumann, and finally the lower and upper bounds. Finally, the performance of lower and upper bounds, derived from direct simulation of Monte Carlo were evaluated through various cases where the uncertainty lies in the different coefficients composing the equation bending as a variational problem. The method proved to be efficient, both in the response of the convergence point as regards the computational cost.